Using Image Synthesis Frameworks to Produce Stereoscopic Views for Mobile AR: a Comparative Study - Hansen, Mikkel G; Lavrinovics, Ernests; Sørensen, Julie U; Debarba, Henrique G (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
This paper investigates different methods for generating stereoscopic views for a head-mounted smartphone augmented reality (AR). Four conditions were compared, a reference stereoscopic video, produced using two mobile phone cameras separated by 63mm, a dual camera phone with limited interpupillary distance (12mm), and two stereoscopic stimuli generated from a single monoscopic view, each using a different view synthesis frameworks. The test was carried out in respect to subjective perceived stereoscopic quality using the SAMVIQ quality of experience methodology. Results suggest a significant advantage for the reference and dual video feeds in complex scenes, where the scene content is structurally diverse and significant occlusion exists. The performance of image synthesis framework improve for simpler scenes, where occlusions are few and structures are mostly flat, but remain inferior to the true stereoscopic capture methods.